Optimalisasi Kepuasan Konsumen Indomaret Melalui Analisis Service Quality (Servqual): (Studi Kasus Indomaret Wilayah Magelang) (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2022)
The rate of growth and development of retail companies in Indonesia has increased significantly which has led to increasingly high competition between companies so that companies must pay attention to competitive advantages, one of which is service quality. Indomaret as one of the largest retail companies in Indonesia, of course, also needs to pay attention to service quality to increase the company's competitive advantage. This study aims to determine how much the level of consumer satisfaction with the services provided by Indomaret in the Magelang area through a questionnaire so that it can help Indomaret to optimize customer satisfaction. This research method uses a qualitative method in the form of a questionnaire, while the questionnaire data processing uses the ServQual approach. Based on primary data obtained by researchers through a questionnaire, namely a number of 68 samples, it was found that the level of service quality provided by Indomaret in the Magelang region scored more than zero which means that the level of customer satisfaction has been able to exceed consumer expectations and to optimize consumer satisfaction Indomaret must pay more attention to reliability dimension.